Development of an Integrated PhET and Augmented Reality Package in a Flipped Classroom to Improve Conceptual Understanding of Renewable Energy - Nada Dhenia Febriyanti; Muhammad Nur Hudha; Riezky Maya Probosari; Annisa Nur Khasanah; Supurwoko Supurwoko; Nada Dhenia Febriyanti; Muhammad Nur Hudha; Riezky Maya Probosari; Annisa Nur Khasanah (Universitas Negeri Malang, 2026)
Renewable energy is an abstract topic in junior high school science: its systems and energy conversions are difficult to visualize, and teacher-centered instruction often leaves students with fragile, fragmented conceptual understanding. This study developed and evaluated a learning package that integrates PhET virtual-laboratory simulations with augmented reality (AR) 3D visualizations, delivered through a flipped-classroom approach, and examined its feasibility, practicality, and effectiveness for Grade IX students' conceptual understanding of renewable energy. Following the ADDIE Research and Development model, PhET simulations and AR scenes (authored in Assemblr Edu) were integrated into a flipped lesson in which first exposure occurred before class and class time was used for manipulation and discussion. Feasibility was assessed by media, content, and language experts using the Gregory index; practicality by teacher and student response questionnaires; and effectiveness by a 25-item conceptual-understanding test (pretest–posttest, n = 34) analyzed with the Hake normalized gain (N-gain) after confirming item construct validity. The package was very valid (media Gregory index 0.89; content and language 1.00), highly practical (student 91% and 81%; teacher 93%), and, in a single-group pretest–posttest design, associated with a medium gain (mean N-gain 0.50; scores rose from 81.18 to 91.53). Pairing manipulable simulation and spatial AR within a flipped structure was designed to shift learning toward a student-centered, inquiry-oriented process. The package offers a feasible, smartphone-deliverable route to visualizing abstract renewable-energy concepts.